Gender disparity in STEM education: a survey research on girl participants in World Robot Olympiad - Chiang, Feng-Kuang; Tang, Zhonghua; Zhu, Dan; Bao, Xianqing (International journal of technology and design education, 2024)
Robotics competitions boosts the development of STEM education, but gender disparity in this field remains rarely addressed by researchers. This study focused on the World Robot Olympiad (WRO) and tried to explore the gender differences through investigation method. The research questions are as follows: RQ1, what is the tendency of girls' participation in WRO from 2015 to 2019 in terms of the four competition categories and three age groups? RQ2, what advantages and challenges do the all-girl teams have from the perspectives of parents, coaches and students? The results showed that among the 5956 participants in the 2015-2019 WRO finals, girls accounted for only 17.3%. The Open Category that emphasized creativity attracted relatively more girl participants. As age group moved up, the number of girl participants decreased. The qualitative results showed that the focuses of coaches, parents and students was not exactly the same. All-girl team have the advantages in their communication, presentation and collaboration skills but less good at robot building. The results indicated the importance of promoting girl's participation in robot competitions and STEM fields. Coaches, mentors and parents need to provide girls with more support and encouragement in learning STEM subjects, especially at the junior high school level. Organizers of related competitions should give girls more exposure and opportunities by adjusting the mechanism.